Sustainable Community Development Step 4: Develop Sustainability Indicators to Measure Progress - Mickie E. Swisher; Sandra Rezola; James Sterns (EDIS, 2003)
This document discusses the importance of developing sustainability indicators used to measure progress in a sustainable community. The document also includes characteristics of effective indicators and tips about how to develop indicators. This document is FCS7217-Eng, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, IFAS, University of Florida, Gainesville FL 32611. First published: September 2003.